Application of the full-width-at-half-maximum image segmentation method to analyse retinal vascular changes in patients with internal carotid artery stenosis - Jiang, Ligang; Liu, Mengting; Yu, Meiting; Lu, Wei; Zhang, Zhe; Tong, Yuhua (Frontiers in Cell and Developmental Biology, 2024)
Background: To investigate the correlation between retinal vascular changes and ICA stenosis by measuring retinal vessels using full-width-at-half-maximum（FWHM） and intelligent image recognition. Methods:This research selected patients who were admitted to the Vascular Surgery Department of Quzhou People's Hospital from January 2018 to December 2020 and were preparing for Carotid Artery Stenting (CAS). Participants were divided into two groups: without ICA stenosis (Group 0) and with ICA stenosis (Group 1). A total of 109 cases were included in the study, with 50 cases in Group 1 and 59 cases in Group 0.Vascular images of superior temporal zone B of the retina were obtained by spectral domain optical coherence tomography (SD-OCT). The edges of retinal vessels were identified by FWHM.Each vessel of all subjects was measured three times with the FWHM, and the average value was taken to obtain the retinal arteriolar lumen diameter (RALD), retinal arteriolar outer diameter (RAOD), retinal venular lumen diameter (RVLD), and retinal venular outer diameter (RVOD),Arterial Wall Thickness（AWT),Venular Wall Thickness（VWT)＝(RVOD-RVLD)/2,Arteriovenous Ratio（AVR）=RAOD/RVOD. Results:We found that compared to Group 0, Group 1 had smaller RALD(P <0.001) and RAOD(P <0.001), and wider RVOD(P <0.001), with thicker VWT(P <0.001). When compared with the contralateral eye in Group 1, the ipsilateral eye exhibited even smaller RALD ,RAOD and AVR(P <0.001,P <0.001,P <0.001).After CAS, the RALD ,RAOD and AVR in Group 1 increased（P <0.001,P <0.001,P <0.001),while the RVLD and RVOD decreased(P <0.05,P<0.001). Our research reveals a significant correlation between retinal vascular changes and internal ICA stenosis. Conclusion:Utilizing SD-OCT in conjunction with the FWHM,we achieved a non-invasive, intelligent, stable, and precise acquisition of data pertaining to retinal vessels.These findings underscore a significant correlation between alterations in retinal vascular structure and the presence of ICA stenosis, as demonstrated by our research.